Water-in-oil composition

By combining surface treatment zinc oxide and suitable oils, a water-in-oil composition with excellent water resistance and useability was prepared, which solved the problems of low water resistance and poor useability of the coating film in the prior art.

CN112969443BActive Publication Date: 2025-04-18KOSE CORPORATION
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN201980075269.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-11-16
Filing Date
2019-10-29
Publication Date
2025-04-18
Estimated Expiration
2039-10-29

AI Technical Summary

Technical Problem

In the prior art, the water-in-oil composition is prone to emulsification when the coating film comes into contact with water, resulting in low water resistance and poor viscosity and useability.

Method used

An excellent water-in-oil composition was prepared by using zinc oxide surface treated with silica and hydrophobizing agent and mixing in a specific ratio in a water/ethanol solvent, combining polar oil and silicone oil, and controlling the content of the surfactant below 1%.

Benefits of technology

The uniformity, water resistance, time stability and useability of the coating film are achieved, and the problems of stickiness and poor useability are avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 355648
    Figure 355648
  • Figure 559120
    Figure 559120
  • Figure DEST_PATH_IMAGE001
    Figure DEST_PATH_IMAGE001
Patent Text Reader

Abstract

The present invention aims to provide a water-in-oil type composition having excellent uniformity, water resistance, and stability over time in a coating film, and having good usability such as no stickiness. The water-in-oil type composition for solving this problem contains the following components (A) to (D): component (A) 5 to 30% by mass of zinc oxide surface-treated with silica and a hydrophobic treatment agent, component (B) polar oil, component (C) silicone oil, and component (D) water; when component (A) is mixed in a water / ethanol solvent (mass ratio water:ethanol=3:1) at 0.25% by mass, the transmittance of light with a wavelength of 700 nm is 0.8 to 20, and the water-in-oil type composition is characterized in that the content of the surfactant is 1% by mass or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a water-in-oil type composition, and more particularly to a water-in-oil type composition having excellent uniformity, water resistance, stability over time, and usability of a coating film. Background Art

[0002] In recent years, there has been a strong demand for skin topical preparations and cosmetics to shield the skin from the adverse effects of ultraviolet rays in sunlight and protect the skin from the adverse effects of ultraviolet rays. Skin topical preparations and cosmetics having ultraviolet protection effects have been developed by incorporating metal oxide powders such as zinc oxide and titanium oxide. However, high water resistance is often required during sports, sea bathing, etc.

[0003] As external preparations for skin and cosmetics having ultraviolet protection effects, technologies of water-in-oil compositions have been disclosed (for example, see Patent Documents 1 and 2).

[0004] Patent Document 1 discloses a sunscreen cosmetic having a high internal phase water-in-oil ratio of 50% by mass or more, comprising: (A) 0.1 to 10% by mass of a cross-linked polyglycerol-alkyl co-modified silicone and (B) an ultraviolet absorber.

[0005] Patent document 2 discloses a water-in-oil emulsified sunscreen cosmetic, characterized in that it contains: (a) hydrophobized zinc oxide and hydrophobized titanium oxide: 10 to 30% by mass, (b) a lipophilic nonionic surfactant: 0.5 to 5% by mass, (c) one or more oils selected from N-lauroyl L-glutamate di(phytosteryl, 2-octyldodecyl) ester, macadamia fatty acid phytosteryl ester, and macadamia fatty acid cholesteryl ester: 1 to 5% by mass, (d) volatile silicone oil and / or hydrocarbon oil: 10 to 40% by mass, and (e) water: 5 to 30% by mass.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Publication No. 2016-145157

[0009] Patent Document 2: Japanese Patent Application Publication No. 2013-43875

[0010] Patent Document 3: Japanese Patent Application No. 2001-518111

[0011] Patent Document 4: Japanese Patent Application Publication No. 2008-208045

[0012] Patent Document 5: Japanese Patent No. 6334167

[0013] Non-patent document 1: B. Binks et al, Advances in Colloid and Interface Science 100-102, 503-546 (2003).

[0014] Effects of the Invention

[0015] Problems to be solved by the invention

[0016] Regarding the technology of Patent Document 1, in skin external preparations and cosmetics having UV protection effects, since the water-in-oil type composition has an oil as the external phase, it is difficult to dissolve in water, and therefore high water resistance is expected, but since a specific amount of cross-linked polyglycerol-alkyl co-modified silicone must be contained, the coating film is emulsified when it comes into contact with water, and the water resistance of the coating film is low. As a result, there are cases where metal oxides and the like peel off and the UV protection effect is poor.

[0017] The technique of Patent Document 2 requires a specific amount of surfactant, and as a result, there is a case where the coating film is strongly sticky and the usability is deteriorated. In addition, since the coating film is emulsified when it comes into contact with water, there is a case where the water resistance is reduced.

[0018] Therefore, the present inventors have attempted to develop a water-in-oil composition having improved water resistance by utilizing a Pickering emulsion emulsified using powders (see, for example, Patent Documents 3 to 5 and Non-Patent Document 1) in order to stably contain metal oxide powders such as zinc oxide and titanium oxide.

[0019] The technology of Patent Document 3 discloses an emulsifier-free cosmetic or dermatological preparation representing an oil-in-water fine dispersion system, which contains: 1) an oil phase, 2) an aqueous phase, and 3) one or more fine inorganic pigments, and optionally contains other cosmetic or pharmaceutical substances as auxiliary additives and / or active agents; the one or more fine inorganic pigments a) have an average particle size of less than 200 nm, and its particles have b) both hydrophilic and lipophilic properties, thereby having amphiphilic characteristics and are arranged along the water / oil interface, and c) are selected from metal oxides, and d) optionally have a surface film.

[0020] Patent document 4 discloses a water-in-oil emulsion composition, characterized in that it contains: (a) 1 to 40% by mass of a powder component that is not dispersed in water, (b) 0.001 to 1% by mass of a hydrophilic surfactant, (c) an oil phase component, and (d) an aqueous phase component.

[0021] Patent document 5 discloses a cosmetic composition in the form of a water-in-oil emulsion comprising: a) a continuous phase as an oily phase,

[0022] b) as a dispersed phase of the aqueous phase, and

[0023] c) particles having a number average particle size of 200 nm or more and 1 μm or less and surface-treated with at least one N-acylated glutamate;

[0024] wherein the N-acylated glutamate is ionically bonded to the particle via a hydroxide of a metal selected from Mg, Al, Ca, and Zn,

[0025] The particles are present at the interface between the continuous phase and the dispersed phase, and

[0026] The cosmetic composition comprises at least one emulsifier in an amount of 1% by weight or less relative to the total weight of the composition.

[0027] However, even if the techniques of Patent Documents 3 to 5 are adopted, the coatings have a strong tackiness and lack of usability due to the greasy feel, and the coatings still have poor uniformity and water resistance. In addition, the coatings may also have poor stability over time depending on the type of oil contained.

[0028] That is, a water-in-oil type composition which is excellent in uniformity, water resistance and stability over time of the coating film and has good usability such as no stickiness has not been known so far.

[0029] Means for solving problems

[0030] The present inventors focused on powders and further conducted in-depth research on zinc oxide surface-treated with silica and a hydrophobic treatment agent to obtain a water-in-oil type composition that solves the above-mentioned problems. As a result, it was found that the following water-in-oil type composition has excellent uniformity and water resistance of the coating film, good stability over time, and excellent usability. The water-in-oil type composition contains zinc oxide surface-treated with silica and a hydrophobic treatment agent, and has a transmittance of 0.8 to 20% for light of a wavelength of 700 nm when mixed in a water / ethanol solvent (mass ratio water:ethanol=3:1) at 0.25 mass%, and further contains a specific content and polar oil and silicone oil, and the content of a surfactant is 1 mass% or less.

[0031] That is, the present invention provides a water-in-oil type composition comprising the following components (A) to (D):

[0032] Component (A) 5 to 30% by mass of zinc oxide surface-treated with silica and a hydrophobic treatment agent

[0033] Ingredient (B) Polar oil

[0034] Ingredient (C) Silicone oil

[0035] Ingredient (D) water;

[0036] When the component (A) is mixed in a water / ethanol solvent (mass ratio water:ethanol=3:1) at 0.25 mass %, the transmittance of light with a wavelength of 700 nm is 0.8 to 20%.

[0037] The content of the surfactant is 1% by mass or less.

[0038] Provided is a water-in-oil composition, wherein the water-in-oil composition is a Pickering emulsion.

[0039] Provided is a water-in-oil type composition, wherein the content of the component (B) is 5 to 30% by mass.

[0040] Provided is a water-in-oil type composition, wherein the content mass ratio (B) / (C) of the component (B) to the component (C) is 0.1 to 8.

[0041] Provided is a water-in-oil composition, wherein an average particle size of emulsion droplets of the water-in-oil composition is 10 to 500 μm.

[0042] Provided is a water-in-oil type composition comprising, as the component (B), a polar oil that is liquid at 25° C. and a polar oil that is solid at 25° C.

[0043] Provided is a water-in-oil type composition, wherein the content mass ratio of the water phase to the oil phase (water phase) / (oil phase) is 0.3 to 5.

[0044] Provided is a water-in-oil type composition, wherein the content mass ratio of the aqueous phase to the component (A) (aqueous phase) / (A) is 0.75 to 10.

[0045] Effects of the Invention

[0046] According to the present invention, a water-in-oil type composition having excellent uniformity of coating film, water resistance, stability over time and usability can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 : Figure 1 0.1 g of the components (1) to (5) in Tables 1 to 4 were weighed in such a manner as to achieve 0.25% by mass relative to 40 g of a water / ethanol mixed solvent (mass ratio of water:ethanol=3:1), and immediately after the weighing, the components were mixed using a vibrator YS-8D (manufactured by YAYOI Co., Ltd.) at 250 times / minute for 30 seconds. Then, 3.5 g were added to a plastic cell having an optical path length of 10 mm × an optical path width of 10 mm, and a photograph was taken of the appearance of the solution 3 minutes after the mixing. The samples were, from the left, solutions of component (1), component (2), component (3), component (4), and component (5).

[0048] Figure 2 : Figure 2The images are obtained by observing component (1), i.e., MZY-500SHE (manufactured by TAYCA), component (2), i.e., FINEX-52W-LP2 (manufactured by Sakai Chemical Industry Co., Ltd.), and component (4), i.e., MZ-500 (manufactured by TAYCA) in Tables 1 to 4 using a transmission electron microscope (H-7650, manufactured by Hitachi High Technologies, Inc.) (measurement conditions: accelerating voltage 80 kV). DETAILED DESCRIPTION

[0049] The present invention will be described in detail below. It should be noted that in the present specification, "to" means a range including numerical values ​​before and after it.

[0050] The component (A) in the present invention is zinc oxide surface-treated with silica and a hydrophobizing agent, and has a transmittance of light at a wavelength of 700 nm (hereinafter sometimes simply referred to as “transmittance”) of 0.8 to 20% when mixed at 0.25% by mass in a water / ethanol solvent (mass ratio water:ethanol=3:1).

[0051] The zinc oxide in the component (A) of the present invention is a powder capable of shielding ultraviolet rays by absorbing, scattering, reflecting, extinguishing, etc., and the particle size and shape are not particularly limited.

[0052] The average particle size of the zinc oxide of the component (A) of the present invention is not particularly limited, but is preferably 1 to 200 nm, more preferably 10 to 100 nm, from the viewpoint of ease of handling when blended into perfumes and cosmetics and stability over time.

[0053] The average particle size of zinc oxide, which is the component (A) of the present invention, is measured by using a scanning electron microscope and is calculated from the results of measuring the particle sizes of 100 particles in an arbitrary field of view.

[0054] The shape of the zinc oxide as the component (A) of the present invention is not particularly limited, but is preferably amorphous from the viewpoint of stability over time and usability, and more preferably has an aspect ratio (major axis diameter / minor axis diameter) of 1.2 to 1.6.

[0055] The silica in the component (A) of the present invention is not particularly limited, and those generally used in cosmetics and skin external preparations can be used. In the component (A) of the present invention, when a hydrophilizing agent such as polyethylene glycol or a hydrophilic surfactant is used instead of silica, since the hydrophilicity of these agents is insufficient, the selective orientation of the component (A) to the oil-water interface may be poor, and the stability over time may not be excellent.

[0056] The hydrophobic treatment agent in the component (A) of the present invention can use those used in the known surface treatment methods. For example, the surface treatment can be carried out by fluoride treatment, silicone treatment, silicone resin treatment, pendant treatment, silane coupling agent treatment, titanium coupling agent treatment, fatty acid treatment, silane treatment, oil treatment, N-acylated lysine treatment, dextrin treatment, ceramide treatment, metal soap treatment, metal oxide powder treatment and the like, or one or more of them can be used for surface treatment. Among these hydrophobic treatment agents, from the aspects of orientation and dispersibility of component (A) to the oil-water interface and stability over time, it is preferably selected from silicone treatment, silane coupling agent treatment, titanium coupling agent treatment, fatty acid treatment One or more, more preferably selected from silicone treatment, silane coupling agent treatment, fatty acid treatment One or more.

[0057] In the present invention, the transmittance of light at a wavelength of 700 nm when mixed at 0.25% by mass in a water / ethanol solvent (mass ratio water:ethanol=3:1) can be measured as follows.

[0058] 0.1 g of component (A) was weighed to 0.25% by mass relative to 40 g of a water / ethanol mixed solvent (mass ratio water: ethanol = 3:1), and immediately after the weighing, the mixture was mixed using a vibrator YS-8D (manufactured by YAYOI Co., Ltd.) at 250 times / minute for 30 seconds. After mixing, 3.5 g was added to a plastic cell with an optical path length of 10 mm × an optical path width of 10 mm, and the solution at the time of 3 minutes after mixing was measured using a spectrophotometer UV-2500PC (manufactured by Shimadzu Corporation) at a wavelength of 700 nm. In addition, a water / ethanol mixed solvent (mass ratio water: ethanol = 3:1) can be used as a reference.

[0059] It is believed that the transmittance of light with a wavelength of 700nm when mixed at 0.25% by mass in a water / ethanol solvent (mass ratio water: ethanol = 3: 1) in the present invention can represent the degree of hydrophilicity and hydrophobicity of the surface of the powder dispersed in the solvent. The reasons are as follows. A water / ethanol mixed solvent (mass ratio water: ethanol = 3: 1) can be said to be a highly hydrophilic solvent. If the hydrophobicity of the surface of the powder dispersed in the solvent is high, the wettability of the powder surface is low, so the powder moves to the gas-liquid interface and the transmittance becomes higher. On the other hand, if the hydrophilicity of the surface of the powder dispersed in the solvent is high, the wettability of the powder surface becomes high, so the powder does not move to the gas-liquid interface and the transmittance becomes lower. Based on the above, it is believed that the transmittance of light with a wavelength of 700nm when mixed at 0.25% by mass in a water / ethanol solvent (mass ratio water: ethanol = 3: 1) is related to the hydrophilicity and hydrophobicity of the surface of the powder dispersed in the solvent.

[0060] In the present invention, the transmittance of light of a wavelength of 700 nm when component (A) is mixed in a water / ethanol solvent (mass ratio water:ethanol=3:1) at 0.25 mass % is not particularly limited as long as it is in the range of 0.8 to 20%, but from the viewpoint of temporal stability, the transmittance is preferably 1 to 18%, more preferably 1 to 16%, and even more preferably 3 to 12%.

[0061] The method for adjusting the transmittance of light of a wavelength of 700 nm when the component (A) in the present invention is mixed at 0.25 mass % in a water / ethanol solvent (mass ratio water: ethanol = 3: 1) is not particularly limited and can be achieved by a known surface treatment method, for example, by appropriately changing the surface treatment amount of silica and a hydrophobic treatment agent, or by appropriately changing the particle size of silica, etc. Specifically, by increasing the surface treatment amount of silica, etc., the transmittance tends to become lower, and by increasing the surface treatment amount of a hydrophobic treatment agent, etc., the transmittance tends to become lower.

[0062] The amount of each of the silica and the hydrophobic treatment agent in the component (A) of the present invention is not particularly limited. In terms of temporal stability, the amount of silica treatment is preferably 0.5 to 10% by mass, more preferably 1 to 4% by mass, relative to the mass of zinc oxide in the component (A). In terms of temporal stability, the amount of hydrophobic treatment agent treatment is preferably 0.5 to 20% by mass, more preferably 1 to 10% by mass, relative to the mass of zinc oxide in the component (A).

[0063] When the component (A) in the present invention is not contained, and the transmittance of the light of the wavelength 700nm when the surface treatment is carried out by silica and a hydrophobic treatment agent and mixed with 0.25 mass% in a water / ethanol solvent (mass ratio water: ethanol = 3: 1) is less than 2% of zinc oxide, sometimes the stability over time is not excellent, and then the water resistance and usability are also poor. In addition, when the component (A) in the present invention is not contained, and the transmittance of the light of the wavelength 700nm when the surface treatment is carried out by silica and a hydrophobic treatment agent and mixed with 0.25 mass% in a water / ethanol solvent (mass ratio water: ethanol = 3: 1) exceeds 20%, sometimes the stability over time is not excellent, and then the water resistance and usability are also poor.

[0064] In the present invention, examples of commercially available products of the component (A) include MZY-500SHE (manufactured by TAYCA Corporation).

[0065] Figure 2The images are obtained by observing component (1) MZY-500SHE (manufactured by TAYCA), component (2) FINEX-52W-LP2 (manufactured by Sakai Chemical Industry Co., Ltd.), and component (4) MZ-500 (manufactured by TAYCA) in Tables 1 to 3 using a transmission electron microscope (H-7650, manufactured by Hitachi High Technologies, Inc.) (measurement conditions: acceleration voltage 80 kV). Figure 2 It can be seen that component (4) has unclear particle outlines and overall particle contrast, and thus has the characteristic that silicon dioxide, which has a lower electron density than zinc oxide, is densely coated on the surface of zinc oxide. In addition, component (2) has clear particle outlines and overall particle contrast, and has the characteristic that it is composed only of zinc oxide. On the other hand, component (1) has slightly unclear particle outlines, but clear overall particle contrast, and has the characteristic that silicon dioxide, which has a lower electron density than zinc oxide, is coated on the surface of zinc oxide in a spot-like manner, and it is believed that the difference in these surface states can be identified.

[0066] In the present invention, the content of component (A) is 5 to 30% by mass relative to the total amount of the water-in-oil type composition. If the content of component (A) is less than 5% by mass, water resistance and temporal stability may be poor, and if it exceeds 30% by mass, usability may be poor. The content of component (A) is not particularly limited as long as it is 5 to 30% by mass, but is preferably 8 to 30% by mass, and particularly preferably 10 to 25% by mass from the perspective of water resistance and temporal stability.

[0067] The polar oil as the component (B) in the present invention is an oil having polarity, and those generally used in cosmetics and external skin preparations can be used.

[0068] The polar oil of component (B) is not particularly limited, and examples thereof include tri(caprylic acid / capric acid) glyceryl, tri(2-ethylhexanoic acid) glyceryl, triisostearic acid glyceryl, triisostearic acid diglyceryl, triisopalmitic acid glyceryl, tricaprylic acid glyceryl, cetyl isooctanoate, isopropyl myristate, isopropyl palmitate, octyldodecyl myristate, tricaprylic acid glyceryl, diisostearic acid polyglyceryl, triisostearate diglyceryl, tribehenic acid glyceryl, pentaerythritol rosinate, neopentyl glycol dioctanoate, cholesterol fatty acid esters, di(cholesteryl / behenyl / octyldodecanol) N-lauroyl-L-glutamate, cetyl isooctanoate, hexyl laurate, isopropyl isostearate, isopalmitoyl Octyl adipate, diisopropyl adipate, di(2-ethylhexyl) adipate, diethyl sebacate, diisopropyl sebacate, dioctyl sebacate, isononyl isononanoate, isotridecyl isononanoate, diester succinate, hydrogenated castor oil stearate, jojoba oil, hexadecyl 2-ethylhexanoate, phytosteryl fatty acid esters, diisostearyl malate, tri(tridecyl) trimellitate, tri(2-ethylhexyl) trimellitate, alkyl benzoate (C12-15), sebacic acid diisopropyl ester, diethylpentylene glycol dipivalate, methylpentylene glycol dipivalate, etc., oils used as ultraviolet absorbers, for example, as benzophenone-based oils, there are 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid, 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid sodium, 2,2'-dihydroxy-4,4'-dimethoxybenzophenone, 2,2'-dihydroxy-4,4'-dimethoxybenzophenone-5-sulfonic acid Sodium, 2,4-dihydroxybenzophenone, 2,2',4,4'-tetrahydroxybenzophenone, 2,4,6-triphenylamino-p-(carbon-2'-ethylhexyl-1'-oxy)-1,3,5-triazine, 2,4-bis[{4-(2-ethylhexyloxy)-2-hydroxy}-phenyl]-6-(4-methoxyphenyl)-(1,3,5)-triazine, 2-2'-methylene-bis-{6-(2H-benzotriazol-2-yl)-4-(1,1,3,Examples of the PABA series include p-aminobenzoic acid, ethyl p-aminobenzoate, glyceryl p-aminobenzoate, amyl p-dimethylaminobenzoate, 2-ethylhexyl p-dimethylaminobenzoate, ethyl p-dihydroxypropylbenzoate, 2-{4-(diethylamino)-2-hydroxybenzoyl}hexylbenzoate, and examples of the cinnamic acid series include 2-ethylhexyl p-methoxycinnamate, 4-methoxycinnamate, Cinnamic acid-2-ethoxyethyl ester, etc., salicylic acid-based compounds include salicylic acid-2-ethylhexyl ester, salicylic acid phenyl ester, salicylic acid homomenthyl ester, etc., and dibenzoylmethane-based compounds include 4-tert-4'-methoxydibenzoylmethane, etc., and 2-2'-methylene-bis-{6-(2H-benzotriazol-2-yl)-4-(1,1,3,3-tetramethylbutyl)phenol}, etc., which can be used alone or in combination of two or more.

[0069] Among them, from the viewpoint of stability over time and usability, it is preferred to contain a polar oil that is liquid at 25°C as component (B). Furthermore, as the polar oil that is liquid at 25°C, it is preferred that one or more selected from triglycerides such as tri(caprylic acid / capric acid)glyceryl, tri(2-ethylhexanoic acid)glyceryl, triisostearic acid glyceryl, triisopalmitic acid glyceryl, and tricaprylic acid glyceryl, 2-ethylhexyl p-methoxycinnamate, isopropyl myristate, alkyl benzoate (C12-15), diisopropyl adipate, diisopropyl sebacate, and isononyl isononanoate, and more preferred is one or more selected from isopropyl myristate, alkyl benzoate (C12-15), diisopropyl adipate, and diisopropyl sebacate. It should be noted that the liquid in the present invention refers to those having fluidity at normal temperature (25°C) and normal pressure.

[0070] From the viewpoint of water resistance, it is preferred to contain a polar oil that is solid at 25°C as component (B). The polar oil that is solid at 25°C is preferably selected from 2-{4-(diethylamino)-2-hydroxybenzoyl}benzoic acid hexyl ester, 2,4-bis[{4-(2-ethylhexyloxy)-2-hydroxy}-phenyl]-6-(4-methoxyphenyl)-(1,3,5)-triazine, 2,4,6-tris[{4-(2-ethylhexyloxycarbonyl)anilino]-1,3,5-triazine, 4-tert-butyl-4'- One or more selected from 2-{4-(diethylamino)-2-hydroxybenzoyl}benzoic acid hexyl ester, 2,4-bis[{4-(2-ethylhexyloxy)-2-hydroxy}-phenyl]-6-(4-methoxyphenyl)-(1,3,5)-triazine, 2,4,6-tris[{4-(2-ethylhexyloxycarbonyl)anilino]-1,3,5-triazine, and 4-tert-butyl-4'-methoxydibenzoylmethane. In the present invention, the solid state refers to those that show semi-solid to solid properties at room temperature (25° C.) and normal pressure and have a melting point of 40° C. or above.

[0071] Examples of commercially available products of the polar oil as the component (B) include M Fine Oil CCT-1 (manufactured by Miyoshi Oil & Fats Co., Ltd.), TIO (manufactured by Nissin Oillio Group Co., Ltd.), TISG (manufactured by Premium Alcohol Industries Co., Ltd.), ISOESTERIDE G-NP (manufactured by National Mison Co., Ltd.), UVINUL MC 80, UVINUL MC 80N (manufactured by BASF Japan Co., Ltd.), IPM (manufactured by Nippon Seika Co., Ltd.), FINSOLV TN (manufactured by Innospec Active Chemicals LLC), FineNeo-DIA, FineNeo-iPSE (manufactured by Nippon Seika Co., Ltd.), and SALACOS 99 (manufactured by Nissin Oillio Group Co., Ltd.).

[0072] The content of the polar oil as component (B) used in the present invention is not particularly limited, but is preferably 5 to 30% by mass, more preferably 10 to 25% by mass, based on the total amount of the water-in-oil composition in terms of uniform coating film and excellent usability.

[0073] In the present invention, it is preferred to contain a polar oil that is liquid at 25° C. and a polar oil that is solid at 25° C. as component (B) because the fluidity of the oil phase during coating film formation during coating becomes suitable and a coating film having good water resistance is obtained.

[0074] Furthermore, when a liquid polar oil at 25°C and a solid polar oil at 25°C are contained simultaneously, the content mass ratio of the liquid polar oil at 25°C to the solid polar oil at 25°C (liquid polar oil at 25°C) / (solid polar oil at 25°C) is preferably 1 to 250, more preferably 2.5 to 150, and particularly preferably 3 to 15 from the viewpoint of water resistance.

[0075] As the silicone oil as the component (C) of the present invention, those generally used in cosmetics and external skin preparations can be used.

[0076] The silicone oil as the component (C) of the present invention is not particularly limited, but is preferably liquid at 25° C. from the viewpoint of excellent stability over time and usability. Examples of the silicone oil include dimethylpolysiloxane, methylphenylpolysiloxane, octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane, methylpolytrimethylsiloxane, polyether-modified methylpolysiloxane, oleyl-modified methylpolysiloxane, and polyvinylpyrrolidone-modified methylpolysiloxane, and one or more of them can be appropriately selected and used. Among them, from the perspective of temporal stability and usability, one or more selected from dimethylpolysiloxane of 2 cs at 25°C, dimethylpolysiloxane of 6 cs at 25°C, dimethylpolysiloxane of 10 cs at 25°C, trimethylsiloxane, and cyclomethicone are preferred. From the perspective of temporal stability, one or more selected from cyclomethicone, dimethylpolysiloxane of 2 cs at 25°C, and dimethylpolysiloxane of 6 cs at 25°C are more preferred.

[0077] Examples of commercially available silicone oils of component (C) include KF-96A-1cs / 1, 5cs / 2cs / 5cs / 6cs / 10cs / 20cs / 30cs / 50cs / 100cs / 200cs / 300cs / 350cs / 500cs / 1000cs / 3000cs / 5000cs / 6000cs, KF-96H-10000cs, s / 1, 250,000 cs / 30,000 cs / 50,000 cs / 60,000 cs / 100,000 cs / 300,000 cs / 500,000 cs / 1,000,000 cs, KF-995 / 994, TMF-1.5, KF-50-100 cs / 1000 cs, KF-53, KF-54, KF-56A, KF-54HV (all manufactured by Shin-Etsu Chemical Co., Ltd.), SH-200 C Fluid 5CS / 6CS / 10CS / 20CS / 30CS / 50CS / 100CS / 200CS / 350CS / 500CS / 1000CS / 3000CS / 5000CS / 10000CS / 12500CS / 30000CS / 60000CS / 100000CS / 1000000CS, BY11-040 / 003 / 007 / 014 / 026 / 320, SH-556 Fluid, PH-1555 HRI Cosmetic Fluid, FZ-3156 (all manufactured by Toray and Dow Corning Corporation), etc.

[0078] The content of the silicone oil as component (C) used in the present invention is not particularly limited, but is preferably 3 to 40% by mass, more preferably 5 to 30% by mass, further preferably 7.5 to 20% by mass, and particularly preferably 13 to 18% by mass, based on the total amount of the water-in-oil type composition, in terms of obtaining a uniform coating film and excellent stability over time.

[0079] Although not particularly limited in the present invention, the mass ratio (B) / (C) of component (B) to component (C) is preferably 0.1 to 8, more preferably 0.4 to 3.3, further preferably 1 to 3.3, and particularly preferably 1 to 2 in terms of uniformity of the coating film, stability over time, and usability.

[0080] The water as component (D) in the present invention may be any water generally used in cosmetics and external skin preparations, and is not particularly limited. As the water as component (D), tap water may be used, or purified water purified by distillation or the like, hot spring water, or deep water may be used. In addition, plant extracts such as aloe vera, witch hazel, linalool, cucumber, lemon, lavender, and rose water may be used.

[0081] The amount of the aqueous phase in the water-in-oil composition of the present invention is not particularly limited, but is preferably 10 to 60% by mass, more preferably 20 to 55% by mass, and even more preferably 30 to 50% by mass from the perspective of excellent stability over time and usability. In the present invention, components having an octanol / water partition coefficient of less than 1 can constitute the aqueous phase. Specifically, aqueous components such as component (D), polyols, water-soluble polymers, water-soluble film-forming resins, and humectants can form the aqueous phase.

[0082] The amount of the oil phase in the water-in-oil composition of the present invention is not particularly limited, but is preferably 20 to 60% by mass, and more preferably 25 to 50% by mass, from the perspective of excellent stability over time and usability. It should be noted that the amount of the oil phase in the water-in-oil composition of the present invention is calculated by excluding the amount of component (A). In the present invention, components having an octanol / water partition coefficient of 1 or more can constitute the oil phase. Specifically, component (B), component (C), and other oily components can form the oil phase.

[0083] Although not particularly limited in the present invention, the content mass ratio of the aqueous phase to the oil phase (aqueous phase) / (oil phase) is preferably 0.3 to 5, more preferably 0.7 to 2, from the viewpoint of excellent stability over time and usability.

[0084] The present invention is not particularly limited, but the mass ratio of the aqueous phase to the component (A) (aqueous phase) / (A) is preferably 0.75 to 10, more preferably 1 to 4, from the viewpoint of excellent uniformity, temporal stability, and usability of the coating film.

[0085] The water-in-oil composition of the present invention may contain, in addition to the above-mentioned components (A) to (D), components commonly used in cosmetics and external skin preparations, for example, oily components other than components (B) and (C), powders other than component (A), surfactants, fibers, polyols, water-soluble polymers, water-soluble film-forming resins, aqueous components such as humectants, antioxidants, defoaming agents, cosmetic ingredients, preservatives, fragrances, etc., within a range that does not hinder the effects of the present invention.

[0086] The oily components other than component (B) and component (C) are not particularly limited as long as they are generally used in cosmetics and external skin preparations, and can be hydrocarbons, fats, fluorine-based oils, etc., regardless of their origin, such as animal oil, vegetable oil, synthetic oil, or properties such as semi-solid oil, liquid oil, or volatile oil. Specifically, liquid paraffin, squalane, vaseline, hydrocarbons of polyisobutylene, perfluorodecane, perfluorooctane, perfluoropolyether, and other fluorine-based oils can be mentioned.

[0087] The powders other than component (A) are not particularly limited in shape such as plate-like, needle-like, particle size such as mist-like, microparticles, pigment-grade, particle structure such as porous or non-porous, as long as they are commonly used in cosmetics and external skin preparations. Examples thereof include inorganic powders, bright powders, organic powders, pigment powders, metal powders, composite powders, and the like. Specific examples include iron oxide, carbon black, chromium oxide, chromium hydroxide, Prussian blue, ultramarine and other colored inorganic pigments, talc, muscovite, phlogopite, red mica, biotite, synthetic mica, sericite, synthetic sericite, barium sulfate, kaolin, silicon carbide, bentonite, montmorillonite, diatomaceous earth, aluminum silicate, magnesium aluminum metasilicate, calcium silicate, barium silicate, magnesium silicate, magnesium carbonate, hydroxyapatite, boron nitride and other white powders, titanium oxide coated mica, titanium oxide coated bismuth oxychloride, iron oxide mica titanium, Prussian blue treated mica titanium, carmine treated mica titanium, bismuth oxychloride, fish scale foil, polyethylene terephthalate, aluminum, epoxy laminated powder, polyethylene terephthalate, polyolefin laminated film powder, polyethylene terephthalate, polymethyl methacrylate laminated film powder and other bright powders, hard Organic low molecular weight powders such as zinc stearate and N-acyl lysine, natural organic powders such as silk powder, cellulose powder, and dextrin powder, organic pigment powders such as Red No. 201, Red No. 202, Red No. 205, Red No. 226, Red No. 228, Orange No. 203, Orange No. 204, Blue No. 404, Yellow No. 401, Red No. 3, Red No. 104, Red No. 106, Orange No. 205, Yellow No. 4, Yellow No. 5, Green No. 3, and Blue No. 1, zirconium, barium, or aluminum lakes, or metal powders such as aluminum powder, gold powder, and silver powder, composite powders such as fine titanium oxide-coated mica titanium, barium sulfate-coated mica titanium, and silica containing titanium oxide, fibers such as nylon, polyester, rayon, and cellulose, etc. These powders can be used alone or in combination, and those that have been surface treated or composited can also be used. Examples of the surface treatment agent include fluoride, silicone oil, powder, oil, gelling agent, surfactant and the like.

[0088] Surfactant is not particularly limited as long as it is commonly used in cosmetics, skin external preparations, and can be contained within the scope of not damaging the effect of the present invention, and relative to the total amount of water-in-oil type composition, the content of surfactant is 1% by mass or less. If the content of surfactant exceeds 1% by mass, the uniformity, water resistance and usability of the coating are sometimes poor. The content of surfactant is not particularly limited as long as it is 1% by mass or less, and from the aspect of water resistance and usability, it is preferably 0.6% by mass or less, more preferably 0.3% by mass or less, and further more preferably 0.1% by mass or less.

[0089] The surfactant is not particularly limited, and examples thereof include nonionic surfactants, anionic surfactants, cationic surfactants, and amphoteric surfactants.

[0090] The surfactant is not particularly limited, and specific examples of the nonionic surfactant include sorbitan fatty acid esters, glycerin fatty acid esters, polyglycerin fatty acid esters, propylene glycol fatty acid esters, polyethylene glycol fatty acid esters, sucrose fatty acid esters, polyoxyethylene alkyl ethers, polyoxypropylene alkyl ethers, polyoxyethylene alkylphenyl ethers, polyoxyethylene fatty acid esters, polyoxyethylene sorbitan fatty acid esters, polyoxyethylene sorbitan fatty acid esters, polyoxyethylene glycerin fatty acid esters, polyoxyethylene propylene glycol fatty acid esters, polyoxyethylene castor oil, Polyoxyethylene hydrogenated castor oil, polyoxyethylene phytosteryl ether, polyoxyethylene phytosteryl ether, polyoxyethylene cholesteryl ether, polyoxyethylene cholesteryl ether, polyoxyalkylene modified organopolysiloxane, polyoxyalkylene・alkyl co-modified organopolysiloxane, lauric acid diethanolamide, coconut oil fatty acid diethanolamide, coconut oil fatty acid monoethanolamide, polyoxyethylene coconut oil fatty acid monoethanolamide, lauric acid monoisopropanolamide, coconut oil fatty acid monoisopropanolamide, polyoxypropylene coconut oil fatty acid monoisopropanolamide, alkanolamide, sugar ether, sugar amide, etc. Examples of the anionic surfactant include polyoxyethylene lauryl ether sulfates such as sodium polyoxyethylene lauryl ether sulfate, ammonium polyoxyethylene lauryl ether sulfate, and triethanolamine polyoxyethylene lauryl ether sulfate; alkyl sulfates such as sodium lauryl sulfate and triethanolamine lauryl sulfate; α-olefin sulfonates such as sodium tetradecene sulfonate and potassium tetradecene sulfonate; acyl isethionates such as sodium N-lauroyl isethionate and potassium N-lauroyl isethionate; N-acyl polypeptide salts such as sodium N-coconut oil fatty acid methyl taurine, sodium N-lauroyl methyl taurine, potassium N-coconut oil fatty acid methyl taurine, and sodium lauroyl hydrolyzed silk; and sulfosuccinic acid such as sodium sulfosuccinate. Examples of the cationic surfactant include alkylamine salts, amine salts such as polyamines and amino alcohol fatty acid derivatives, alkyl quaternary ammonium salts, aromatic quaternary ammonium salts, pyridinium salts, imidazolium salts, stearyltrimethylammonium chloride, behenyltrimethylammonium chloride, hexadecyltrimethylammonium chloride, distearyldimethylammonium chloride, dibehenyldimethylammonium chloride, dihexadecyldimethylammonium chloride, stearyldimethylbenzylammonium chloride, dilauryldimethylammonium chloride, dipolyoxyethylene (15EO) coconut oil alkylmethylammonium chloride, dipolyoxyethylene (4EO) lauryl ether dimethylammonium chloride, dicocoylethylhydroxyethylmethylammonium sulfate, distearylethylhydroxyethylmethylammonium methylsulfate, distearylethylhydroxyethylmethylammonium methylsulfate, dipalmitoylethylhydroxyethylmethylammonium methylsulfate, and palmitamidopropyltrimethylammonium chloride.As the amphoteric surfactant, examples of the betaine acetate type surfactant include octyl dimethylaminoacetic acid betaine, lauryl dimethylaminoacetic acid betaine, coconut oil fatty acid amide propyl betaine, coconut oil fatty acid alkyl dimethylaminoacetic acid betaine, myristyl dimethylaminoacetic acid betaine, hexadecyl ester dimethylaminoacetic acid betaine, coconut oil fatty acid amide propyl dimethylaminoacetic acid betaine, lauric acid amide propyl dimethylaminoacetic acid betaine, lauryl dihydroxyethylaminoacetic acid betaine, hexadecyl ester dihydroxyethylaminoacetic acid betaine, and the like. In addition, examples of the imidazoline type surfactant include sodium N-coconut oil fatty acid acyl-N-carboxymethyl-N-hydroxyethylethylenediamine, disodium N-coconut oil fatty acid acyl-N-carboxymethoxyethyl-N-carboxymethylethylenediamine, and the like.

[0091] The antioxidant is not particularly limited as long as it is generally used in cosmetics and external skin preparations, and examples thereof include tocopherol and ascorbic acid. Examples of the preservative include parabens, phenoxyethanol, and 1,2-pentanediol.

[0092] The beauty ingredients are not particularly limited as long as they are generally used in cosmetics and external preparations for skin, and examples thereof include astaxanthin, vitamins, anti-inflammatory agents, and herbal medicines.

[0093] The method for producing the water-in-oil composition of the present invention is not particularly limited. For example, the composition can be obtained by adding any other components to components (A), (B), and (C), heating to 90°C and uniformly mixing, adding an aqueous phase, and emulsifying and mixing using a disperser or the like. Furthermore, as the method for producing the water-in-oil composition of the present invention, it is preferred not to use a rolling process in order to improve the yield of the water-in-oil composition. When zinc oxide, titanium oxide, etc. other than component (A) are contained, a rolling process is often used to improve the dispersibility in the water-in-oil composition, but component (A) in the present invention can be contained without a rolling process because it itself shows high dispersibility in the water-in-oil composition.

[0094] The form of the water-in-oil type composition of the present invention is not particularly limited, and may be in any form, such as liquid, gel, cream, semisolid, solid, or stick.

[0095] The water-in-oil type composition in the present invention is not particularly limited, but is preferably a Pickering emulsion. A Pickering emulsion is an emulsion prepared by allowing a powder to adsorb on an interface (for example, see Non-Patent Document 1).

[0096] The average particle size of the emulsion droplets of the water-in-oil composition of the present invention is not particularly limited, but is preferably 10 to 500 μm, more preferably 20 to 300 μm, and even more preferably 150 to 300 μm in terms of temporal stability and usability.

[0097] The average particle size of the emulsion droplets of the water-in-oil composition of the present invention can be measured by measuring the particle sizes of 100 emulsion droplets at room temperature using an optical microscope (manufactured by OLYMPUS) and calculating the average value thereof.

[0098] When the water-in-oil type composition of the present invention is applied, if the water droplets released from the emulsion droplets are large enough to be observed with the naked eye, it will not be sticky and will have good usability such as tenderness. Therefore, as mentioned above, the average particle size is preferably 10 to 500 μm, more preferably 20 to 300 μm, and even more preferably 150 to 300 μm. When the emulsified particle size of the water-in-oil type composition of the present invention is an appropriate value, it is considered that the size of the water droplets released from the emulsion droplets during application becomes appropriate.

[0099] Furthermore, when the size of water droplets released from the emulsion droplets during coating is appropriate, the localization of the water phase and the oil phase during coating film formation becomes appropriate, resulting in good uniformity of the coating film and excellent water resistance.

[0100] Surprisingly, the average particle size of the emulsion droplets of the water-in-oil type composition of the present invention can be adjusted by adjusting the value of the content mass ratio (B) / (C) of the component (B) and the component (C) in addition to the stirring speed and stirring time in the emulsification mixing process. If the content mass ratio (B) / (C) is increased, the average particle size of the emulsion droplets tends to increase. For example, in order to make the average particle size of the emulsion droplets of the water-in-oil type composition of the present invention 10 to 500 μm, the content mass ratio (B) / (C) is preferably 0.1 to 8, in order to make the average particle size of the emulsion droplets 20 to 300 μm, the content mass ratio (B) / (C) is preferably 0.4 to 3.3, in order to make the average particle size of the emulsion droplets 150 to 300 μm, the content mass ratio (B) / (C) is preferably 1 to 3.3, and in order to make the average particle size of the emulsion droplets 150 to 200 μm, the content mass ratio (B) / (C) is preferably 1 to 2.

[0101] The water-in-oil type composition of the present invention is not particularly limited, and can be used as cosmetics, skin external preparations, etc. As cosmetics, for example, external solid preparations, external liquid preparations, sprays, ointments, creams, gels, patches, etc., emulsions, lotions, facial mask cosmetics, facial cleansers, massage cosmetics, hair cosmetics, sunscreens, body cosmetics such as body creams, eye creams and other eye periorbital cosmetics, lip essences, lipsticks and other lip care cosmetics, foundations, primers, concealers, white powders, eye shadows, blushers, lipsticks, mascara, eyebrow pencils and other cosmetic preparations, etc. As skin external preparations, for example, liniments, lotions, ointments, etc., can be mentioned. Among them, from the aspect of water resistance, sunscreens, eye periorbital cosmetics, lip care cosmetics, and cosmetic preparations are preferred, and sunscreens and cosmetic preparations are more preferred. Example

[0102] The present invention is described in detail below with reference to the following examples, but it should be noted that these examples do not limit the present invention in any way.

[0103] Examples 1 to 21 and Comparative Examples 1 to 9: Water-in-oil sunscreen

[0104] 1. The transmittance of the powder was evaluated by the following (evaluation method) regarding components (1) to (5).

[0105] Furthermore, water-in-oil type sunscreens of the formulations shown in Tables 1 to 4 were prepared, and 2. uniformity of the coating film, 3. water resistance, 4. stability over time, and 5. usability were evaluated by the following (evaluation method). The five items were comprehensively evaluated, and ABC was used as the passing score. Those that obtained the passing score in all the evaluation items were set as acceptable, and the others were set as unacceptable. In addition, for the examples, the particle size of 100 emulsion droplets was measured at room temperature using an optical microscope (manufactured by OLYMPUS), and their average value was calculated to measure the average particle size of the emulsion droplets. These evaluation results are shown in Tables 1 to 4.

[0106] (Evaluation items)

[0107] 1. Transmittance of powder

[0108] 2. Uniformity of coating

[0109] 3. Water resistance

[0110] 4. Stability over time

[0111] 5. Usability.

[0112] (Evaluation method)

[0113] 1. Transmittance of powder

[0114] 0.1 g of components (1) to (5) were weighed to 0.25% by mass relative to 40 g of a water / ethanol mixed solvent (mass ratio water:ethanol = 3:1), and immediately after the weighing, the mixture was mixed using a vibrator YS-8D (manufactured by YAYOI Co., Ltd.) at 250 times / minute for 30 seconds. After mixing, 3.5 g was added to a plastic cell with an optical path length of 10 mm and an optical path width of 10 mm. The solution was measured at a wavelength of 700 nm using a spectrophotometer UV-2500PC (manufactured by Shimadzu Corporation) after 3 minutes of mixing to obtain a measured value (%). In addition, a water / ethanol mixed solvent (mass ratio water:ethanol = 3:1) was used as a reference.

[0115] 2. Uniformity of coating

[0116] Each sample of Examples 1 to 21 and Comparative Examples 1 to 9 was coated on a polymethyl methacrylate plate at a thickness of 50 μm and dried at room temperature for 15 minutes. The SPF values ​​at 10 locations were measured using an SPF analyzer UV-2000S (manufactured by Labsphere). The obtained standard deviation was divided by the average value, and the obtained coefficient of variation was determined based on the following <Determination Criteria 1>.

[0117] <Judgment Criteria 1>

[0118] (Judgment): (value of coefficient of variation)

[0119] A: 0 or more and 0.25 or less

[0120] B: more than 0.25 and less than 0.50

[0121] C: more than 0.50 and less than 0.75

[0122] D: more than 0.75 and less than 1.00

[0123] E: Over 1.00.

[0124] 3. Water resistance

[0125] Each sample of Examples 1 to 21 and Comparative Examples 1 to 9 was coated on a polymethyl methacrylate plate with a thickness of 50 μm, and after drying at room temperature for 15 minutes, the SPF value was measured three times using an SPF analyzer UV-2000S (manufactured by Labsphere), and the average value was taken as the initial value. Then, water at 25°C was added to a tower-shaped water tank container with a diameter of 50 cm and a depth of 15 cm at a depth of 11 cm, and a flat plate with a polymethyl methacrylate plate fixed was set at a distance of 21 cm from the rotating axis of the water tank container and immersed at a depth of 10 cm. In this state, the water tank container was rotated, and the flow rate of the water flow in front of the flat plate was adjusted to 24 to 28 cm / s, and the rotation speed of the water tank container was adjusted to 45 rpm. Then, the polymethyl methacrylate plate coated with each sample was fixed to the flat plate, and the flat plate was fixed in the water tank container at a position 1 cm away from the bottom surface and immersed, and the water tank container was rotated to start a water bath. After 80 minutes, the plate with the polymethyl methacrylate plate fixed was taken out of the water tank container and dried at room temperature for 15 minutes. The SPF value was measured three times in the same way, and the average value was taken as the residual value. The residual rate of the SPF value before and after the water bath treatment was calculated (= (residual value) / (initial value)), and the judgment was made according to the following <Judgment Criteria 2>.

[0126] <Judgment Criteria 2>

[0127] (Judgment): (value of residual rate)

[0128] A: The residual rate exceeds 90%

[0129] B: The residual rate is more than 75% and less than 90%

[0130] C: The residual rate is more than 60% and less than 75%

[0131] D: The residual rate is more than 45% and less than 60%.

[0132] E: The residual rate is 45% or less.

[0133] 4. Stability over time

[0134] 30 g of each sample of Examples 1 to 21 and Comparative Examples 1 to 9 was weighed into a glass bottle (No. 6 specification, PS-NO. 6), and stored in a thermostatic chamber at 50° C. for 1 month. The state of each sample after 1 month was visually confirmed and judged according to the following <Judgment Criteria 3>.

[0135] <Judgment Criteria 3>

[0136] (Judgment): (Appearance status)

[0137] A: No separation of aqueous phase was observed

[0138] B: The separation layer of the aqueous phase was confirmed to be less than 0.5 mm. When each sample was shaken up and down 3 times, the separation layer disappeared.

[0139] C: A separation layer of the aqueous phase was confirmed to be more than 0.5 mm and less than 1.0 mm. When each sample was shaken up and down 3 times, the separation layer disappeared.

[0140] D: The separation layer of the aqueous phase was confirmed to be more than 1.0 mm and less than 1.5 mm. When each sample was shaken up and down 3 times, the separation layer disappeared.

[0141] E: A separation layer of the aqueous phase was confirmed to be more than 1.5 mm and less than 1.0 mm, and the separation layer did not disappear even when each sample was shaken up and down three times.

[0142] 5. Usability

[0143] Women aged 20 to 40 were trained in sensory evaluation, and 10 expert judges who could evaluate according to a certain standard were selected. The expert judges applied 5 g of each sample of Examples 1 to 21 and Comparative Examples 1 to 9 to the upper arm, and gently drew a circle with the middle and ring fingers of the other hand to apply it. The usability felt at this time was evaluated and scored in 5 stages according to the following <Absolute Evaluation Standard>. For each sample, the average score was calculated from the total score of all judges, and judgment was made according to the following <Judgment Standard 4>.

[0144] <Absolute Evaluation Criteria>

[0145] (Rating): (Usability)

[0146] 5 points: Water droplets were observed within 5 circles when applying, and the skin did not feel sticky and was very tender.

[0147] 4 points: Water droplets are observed when the application is made in more than 5 circles and within 10 circles, and the skin does not feel sticky and is tender.

[0148] 3 points: When applying more than 10 circles, no water droplets are observed, but the stickiness is hardly felt.

[0149] 2 points: When applying, no water droplets are observed when the circle is drawn more than 10 times, and it feels slightly sticky and is applied more than 15 times, and water droplets are observed within 20 times.

[0150] 1 point: No water droplets were observed when the application was made in more than 10 circles, but strong stickiness was felt.

[0151] <Judgment Criteria 4>

[0152] (Judgment): (average score)

[0153] A: 4.2 points or above: Very good

[0154] B: Less than 4.2 points and 3.4 points or more: Good

[0155] C: Less than 3.4 points and 2.6 points or more: Slightly good

[0156] D: Less than 2.6 points and 1.8 points or more: Slightly poor

[0157] E: Less than 1.8 points: Poor.

[0158]

[0159]

[0160]

[0161]

[0162] ※1: MZY-500SHE (produced by TAYCA) Average particle size 25nm, amorphous

[0163] ※2: FINEX-52W-LP2 (manufactured by Sakai Chemical Industry Co., Ltd.) Average particle size 20nm, irregular shape

[0164] ※3: MZY-505S (produced by TAYCA) Average particle size 25nm, amorphous

[0165] ※4: MZ-500 (produced by TAYCA) Average particle size 25nm, amorphous

[0166] ※5: NAI-Titanium MP-1133 (Made by Miyoshi Chemicals Co., Ltd.) Average particle size 250nm

[0167] ※6: D-400 (manufactured by Negami Industries) Average particle size 15 μm

[0168] ※7: Tospearl 2000B (Momentive Performance Material Japan Co., Ltd.) Average particle size 6 μm

[0169] *8: PEMULEN TR-1 (manufactured by Lubrizol Advanced Materials).

[0170] (Manufacturing method)

[0171] A: Components (6) to (13) are uniformly mixed and dissolved at 80°C.

[0172] B: Components (1) to (5) and components (14) to (22) are uniformly mixed and dispersed using a roll mill, and then mixed with A.

[0173] C: Mix ingredients (23) to (29) uniformly.

[0174] D: C was added to B, and emulsified using a disperser at 2000 rpm at room temperature for 5 minutes.

[0175] E: D is filled into a container to obtain a water-in-oil type sunscreen.

[0176] As is clear from the results in Table 1, the water-in-oil type sunscreens of Examples 1 to 5 of the present invention are excellent in uniformity of the coating film, water resistance, stability over time, and usability.

[0177] On the other hand, in Comparative Example 1, which did not contain component (A) but used zinc oxide whose surface was treated with silica and a hydrophobic treatment agent and whose transmittance of light at a wavelength of 700 nm was not 0.8 to 20% when mixed in a water / ethanol solvent (mass ratio water:ethanol=3:1) at 0.25 mass %, the uniformity, temporal stability and usability of the coating film were poor. This is considered to be because component (2) did not exert its amphiphilicity and therefore emulsification did not occur well.

[0178] In Comparative Example 2, which did not contain component (A) but used zinc oxide that was surface-treated with a hydrophobic treatment agent and had a transmittance of 0.8 to 20% at a wavelength of 700 nm when mixed in a water / ethanol solvent (mass ratio water:ethanol=3:1) at 0.25 mass %, the uniformity, temporal stability, and usability of the coating film were poor. This is believed to be because component (3) did not exert amphiphilicity and thus emulsification did not occur well.

[0179] In Comparative Example 3, which did not contain component (A) but used untreated zinc oxide whose transmittance at a wavelength of 700 nm was not 0.8 to 20% when mixed at 0.25% by mass in a water / ethanol solvent (mass ratio of water:ethanol=3:1), the uniformity, water resistance, stability over time, and usability of the coating film were poor. This is considered to be because component (4) did not exert its amphiphilicity and thus emulsification did not occur well.

[0180] In Comparative Example 4, in which titanium oxide was treated with 2Na stearoyl glutamate and the transmittance of light at a wavelength of 700 nm was not 0.8 to 20% when titanium oxide was mixed at 0.25% by mass in a water / ethanol solvent (mass ratio water:ethanol=3:1) without component (A), the uniformity, temporal stability, and usability of the coating film were poor. This is considered to be because component (5) had poor selective orientation at the oil-water interface and emulsification did not occur well.

[0181] As can be seen from Table 2, in Comparative Example 5 in which the component (A) was less than 5% by mass, the uniformity, water resistance, stability over time, and usability of the coating film were inferior to those of the Examples. This is considered to be because the amount of the component (A) adsorbed on the interface was insufficient and emulsification did not occur well.

[0182] In Comparative Example 6, in which the content of component (A) exceeded 30% by mass, the uniformity and usability of the coating film were poor. This is considered to be because the excess amount of component (A) that failed to be adsorbed on the interface was dispersed in the oil phase, and the feel of component (A) itself became dominant during coating, and a strong stickiness was felt instead of a moist feel, resulting in poor usability.

[0183] In Comparative Example 7 in which the content of the surfactant exceeded 1% by mass, the uniformity, water resistance, and temporal stability of the coating film were inferior to those of the Examples.

[0184] As can be seen from Table 3, the sunscreens of each example were rated high in each item, and in particular, Examples 1, 14, and 15, in which the emulsion droplets were in the range of 150 to 300 μm, were rated A in all items, and had particularly good usability with a soft texture. In addition, as the content mass ratio (B) / (C) increased, it was observed that the average particle size of the emulsion droplets tended to increase, confirming that in order to make the emulsion droplets in the range of 150 to 300 μm, the content mass ratio (B) / (C) was preferably set in the range of 1 to 3.3.

[0185] On the other hand, in Comparative Example 8 which did not contain the component (B), the uniformity and usability of the coating film were inferior.

[0186] In Comparative Example 9 which did not contain the component (C), the coating film was inferior in uniformity, water resistance, and stability over time.

[0187] Table 4 shows that, compared with Comparative Example 8 not containing the polar oil as component (B), the addition of polar oil significantly improves the uniformity and usability of the coating film. In particular, the combined use of liquid polar oil and solid liquid oil further improves water resistance.

[0188] Example 16: Water-in-oil liquid foundation

[0189] (Ingredients) (Mass %)

[0190] (1) Zinc oxide surface treated with silica and a hydrophobic treatment agent ※9 8

[0191] (2) Titanium dioxide treated with isopropyl titanium triisostearate ※10 8

[0192] (3) Methyl hydrogen polysiloxane treated titanium dioxide ※11 2

[0193] (4) 2-Ethylhexyl methoxycinnamate 5

[0194] (5) 2-{4-(diethylamino)-2-hydroxybenzoyl}benzoic acid hexyl ester 1.5

[0195] (6) 2,4-bis[{4-(2-ethylhexyloxy)-2-hydroxy}-phenyl]-6-

[0196] (4-Methoxyphenyl)-(1,3,5)-triazine 0.5

[0197] (7) Caprylic / capric triglyceride 3

[0198] (8) Hexyl laurate 3

[0199] (9) Hydrogenated polyisobutylene ※12 3

[0200] (10) Cyclomethicone 10

[0201] (11) Methyl trimethicone 5

[0202] (12) Phenyl trimethicone ※13 2

[0203] (13) Lauryl PEG-9 Polydimethylsiloxyethyl Dimethicone 0.2

[0204] (14) Anhydrous silicic acid ※14 1.5

[0205] (15) Triethoxycaprylylsilane treated sericite ※15 2

[0206] (16) Remaining amount of purified water

[0207] (17) Ethanol 5

[0208] (18) Propylene glycol 5

[0209] (19) Phenoxyethanol 0.3

[0210] (20) Hydrolyzed hyaluronic acid 0.5

[0211] (21) Hydrolyzed collagen 0.5

[0212] (22) Theanine 0.5

[0213] (23) Serine 0.2

[0214] (24) Sodium chloride 0.2

[0215] (25) Sorbitol 2

[0216] (26) Tremella polysaccharide 0.01

[0217] (27) Peony bark extract 0.03

[0218] (28) Ascorbic acid 0.001

[0219] ※9: (Evaluation method) 1. The transmittance measured by the method described in the transmittance of powder is 1.5%, and the average particle size is 25nm

[0220] ※10: ITT-2 TiO2 CR-50 (manufactured by KOBO PRODUCTS) Average particle size 250nm

[0221] ※11: MT-05 (produced by TAYCA) Average particle size 10nm

[0222] ※12: PARLEAM 4 (manufactured by NOF Corporation)

[0223] ※13: SH556 FLUID (Toray and Dow Corning)

[0224] ※14: CHIFFONSIL P-3R (manufactured by Nichiren Chemicals Co., Ltd.) Average particle size 5μm

[0225] ※15: OTS-2 Sericite FSE (manufactured by Daito Chemical Industry Co., Ltd.) Average particle size: 10 μm.

[0226] (Manufacturing method)

[0227] A: Components (4) to (8) are uniformly mixed and dissolved at 80°C.

[0228] B: Components (1) to (3) and components (9) to (15) were uniformly mixed and dispersed in a disperser at 2000 rpm at room temperature for 5 minutes, and then mixed with A.

[0229] C: Mix ingredients (16) to (28) uniformly.

[0230] D: C was added to B, and emulsified using a disperser at 2000 rpm at room temperature for 5 minutes.

[0231] E: Fill D into a container to obtain a water-in-oil liquid foundation.

[0232] The water-in-oil liquid foundation of Example 16 was excellent in uniformity of the coating film, water resistance, stability over time, and usability.

[0233] Example 17: Water-in-oil daytime beauty serum

[0234] (Ingredients) (Mass %)

[0235] (1) Zinc oxide surface treated with silica and a hydrophobic treatment agent ※16 10

[0236] (2) Dimethyl polysiloxane treated titanium dioxide ※17 1

[0237] (3) Titanium dioxide treated with triethoxycaprylylsilane ※18 1

[0238] (4) 2-Ethylhexyl methoxycinnamate 5

[0239] (5) 2,4,6-tris[{4-(2-ethylhexyloxycarbonyl)anilino]-1,3,5-triazine 1.5

[0240] (6) Diisopropyl adipate 5

[0241] (7) Isononyl isononanoate 2

[0242] (8) Glyceryl triisostearate 0.1

[0243] (9) Squalane 3

[0244] (10) Astaxanthin 0.002

[0245] (11) Isododecane 3

[0246] (12) Cyclomethicone 10

[0247] (13) Dimethyl polysiloxane ※19 3

[0248] (14) Dimethyl polysiloxane ※20 3

[0249] (15) Sorbitan sesquiisostearate 0.2

[0250] (16) Cross-linked silicone and network-type silicone block copolymers ※21 2

[0251] (17) Polymethyl methacrylate ※22 2

[0252] (18) Remaining amount of purified water

[0253] (19) Ethanol 5

[0254] (20) Tripropylene glycol 5

[0255] (21) Glycerol 2.5

[0256] (22) Diglycerol 0.5

[0257] (23) 1,3-Butanediol 5

[0258] (24) Phenoxyethanol 0.2

[0259] (25) Polyoxyethylene methyl glucoside 0.5

[0260] (26) Acetylated sodium hyaluronate 0.1

[0261] (27) Propylene glycol hyaluronic acid 0.2

[0262] (28) Sodium chloride 0.2

[0263] (29) Erythritol 3

[0264] (30) Shuiqian Temple cyanobacteria polysaccharide 0.05

[0265] (31) Mulberry root bark extract 0.05

[0266] (32) Ascorbyl glucoside 0.2

[0267] ※16: (Evaluation method) 1. The transmittance measured by the method described in the transmittance of powder is 18%, and the average particle size is 25nm

[0268] ※17: SA-titanium MP-1133 (made by Miyoshi Chemicals Co., Ltd.) Average particle size 250nm

[0269] ※18: OTS-2 TiO2 MP-1133 (manufactured by Daito Chemical Industry Co., Ltd.) Average particle size 250nm

[0270] ※19: KF-96A-1.5cs (manufactured by Shin-Etsu Chemical Co., Ltd.)

[0271] ※20: KF-96A-6cs (manufactured by Shin-Etsu Chemical Co., Ltd.)

[0272] ※21: KSP-101 (manufactured by Shin-Etsu Chemical Co., Ltd.) Average particle size 12 μm

[0273] ※22: MATSUMOTO MICROSPHERE M101 (manufactured by Matsumoto Oil & Fats Pharmaceutical Co., Ltd.) Average particle size: 9 μm.

[0274] (Manufacturing method)

[0275] A: Components (4) to (8) are uniformly mixed and dissolved at 80°C.

[0276] B: Components (1) to (3) and components (9) to (17) are uniformly mixed and dispersed using a roll mill, and then mixed with A.

[0277] C: Mix ingredients (18) to (32) uniformly.

[0278] D: C was added to B, and emulsified using a disperser at 2000 rpm at room temperature for 5 minutes.

[0279] E: D is filled into a container to obtain a water-in-oil type daytime beauty serum.

[0280] The water-in-oil daytime beauty serum of Example 17 was excellent in uniformity of the coating film, water resistance, stability over time, and usability.

[0281] Example 18: Water-in-oil makeup primer

[0282] (Ingredients) (Mass %)

[0283] (1) Zinc oxide surface treated with silica and a hydrophobic treatment agent ※23 12

[0284] (2) Titanium dioxide treated with sodium lauroyl aspartate ※24 2.5

[0285] (3) Sodium lauroyl glutamate treated titanium dioxide ※25 2.5

[0286] (4) 2-Ethylhexyl methoxycinnamate

[0287] (5) 2,4,6-tris[{4-(2-ethylhexyloxycarbonyl)anilino]-1,3,5-triazine 1

[0288] (6) 2-{4-(diethylamino)-2-hydroxybenzoyl}benzoic acid hexyl ester 1

[0289] (7) 2,4-bis[{4-(2-ethylhexyloxy)-2-hydroxy}-phenyl]-6-

[0290] (4-Methoxyphenyl)-(1,3,5)-triazine 1

[0291] (8) Triisostearate diglyceride 0.3

[0292] (9) Alkyl benzoate (C12-15) 5

[0293] (10) Tri(2-ethylhexyl) trimellitate 2

[0294] (11) Isododecane 2.5

[0295] (12) Cyclomethicone 14

[0296] (13) Dimethyl polysiloxane ※26 2

[0297] (14) Dimethyl polysiloxane ※27 2

[0298] (15) Trimethylsiloxysilicate 2

[0299] (16) Lauryl Polyglyceryl-3 Polydimethylsiloxyethyl Dimethicone 0.2

[0300] (17) Nylon-12 ※28 3

[0301] (18) Lauroyl lysine 0.1

[0302] (19) Remaining amount of purified water

[0303] (20) Ethanol 3

[0304] (21) 1,2-Pentanediol 0.5

[0305] (22) Phenoxyethanol 0.2

[0306] (23) Dipropylene glycol 3

[0307] (24) 1,3-Butanediol 5

[0308] (25) Polyethylene glycol ※29 2

[0309] (26) (Eicosanedioic acid, Tetradecanedioic acid) Polyglycerol-10 0.1

[0310] (27) Triphenyltriazine 1

[0311] (28) Methylenebisbenzotriazolyltetramethylbutylphenol 1

[0312] (29) Hydroxypropyltrimonium chloride hyaluronic acid 0.3

[0313] (30) Succinyl atelocollagen 0.5

[0314] (31) N-acetyl-L-hydroxyproline 0.5

[0315] (32) Sodium citrate 0.05

[0316] (33) Potassium chloride 0.2

[0317] (34) Ecdoin 1

[0318] (35) (PEG-240・Decyltetradecyl alcohol polyether-20・HDI) copolymer 0.05

[0319] (36) 2-Methacryloyloxyethylphosphorylcholine·Butyl Methacrylate Copolymer Liquid 0.5

[0320] (37) Humus extract 0.05

[0321] (38) Magnesium L-ascorbyl phosphate 0.2

[0322] ※23: (Evaluation method) 1. Transmittance measured by the method described in the transmittance of powder is 5%, average particle size is 25nm

[0323] ※24: ASI TiO2 CR-50 (manufactured by Daito Chemical Industry Co., Ltd.) Average particle size 250nm

[0324] ※25: ASL-1 TiO2 MP-1133 (manufactured by Daito Chemical Industry Co., Ltd.) Average particle size 250nm

[0325] ※26: KF-96A-1cs (manufactured by Shin-Etsu Chemical Co., Ltd.)

[0326] ※27: KF-96A-20cs (manufactured by Shin-Etsu Chemical Co., Ltd.)

[0327] ※28: ORGASOL 2002D (manufactured by Alkama Co., Ltd.) Average particle size 20 μm

[0328] ※29: PEG-400 (manufactured by Toho Chemical Industry Co., Ltd.).

[0329] (Manufacturing method)

[0330] A: Components (4) to (8) are uniformly mixed and dissolved at 80°C.

[0331] B: Components (1) to (3) and components (9) to (16) are uniformly mixed and dispersed using a roll mill, and then mixed with A.

[0332] C: Mix ingredients (17) to (38) uniformly.

[0333] D: C was added to B, and emulsified using a disperser at 2000 rpm at room temperature for 5 minutes.

[0334] E: Fill D into a container to obtain a water-in-oil type makeup primer.

[0335] The water-in-oil cosmetic primer of Example 18 was excellent in uniformity of the coating film, water resistance, stability over time, and usability.

[0336] Example 19: Water-in-oil sunscreen stick

[0337] (Ingredients) (Mass %)

[0338] (1) Zinc oxide surface treated with silica and a hydrophobic treatment agent ※30 8

[0339] (2) Titanium dioxide treated with hydroxypropyl bispalmitamide MEA ※31 2

[0340] (3) Titanium dioxide treated with perfluorooctyltriethoxysilane※32 1

[0341] (4) Titanium dioxide treated with magnesium stearate ※33 1

[0342] (5) 2-Ethylhexyl methoxycinnamate 6

[0343] (6) 2-{4-(diethylamino)-2-hydroxybenzoyl}benzoic acid hexyl ester 1

[0344] (7) 2,4-bis[{4-(2-ethylhexyloxy)-2-hydroxy}-phenyl]-6-

[0345] (4-Methoxyphenyl)-(1,3,5)-triazine 1

[0346] (8) 2,4,6-tris[{4-(2-ethylhexyloxycarbonyl)anilino]-1,3,5-triazine 1

[0347] (9) Diethyl sebacate 4

[0348] (10) Diethylhexyl succinate 4

[0349] (11) Methylpentanediol dipivalate 4

[0350] (12) Dimer linoleic acid (phytosteryl, isostearyl, hexadecyl, stearyl, behenyl) ester 2

[0351] (13) Tocopherol 0.02

[0352] (14) Polyethylene ※34 5

[0353] (15) Microcrystalline wax ※35 4

[0354] (16) Alkanes ※36 2

[0355] (17) Dimethyl polysiloxane ※37 10

[0356] (18) Vaseline 2

[0357] (19) (Dimethicone / Polyglyceryl-3) Crosspolymer 0.1

[0358] (20) (PEG-15・Lauryl Dimethicone) Crosspolymer 0.1

[0359] (21) Anhydrous silicic acid ※38 3

[0360] (22) Polydimethylsiloxane and aminopropyltriethoxysilane treated talc ※39 2

[0361] (23) Remaining amount of purified water

[0362] (24) 1,3-Butanediol 2

[0363] (25) Glycerol 2

[0364] (26) Polyoxyethylene glycerol (26.EO.) 2

[0365] (27) Polyoxypropylene diglyceryl ether 2

[0366] (28) Cyclohexane-1,4-dicarboxylic acid bis(ethoxydiglycol) ester 0.5

[0367] (29) Phenoxyethanol 0.2

[0368] (30) Honeysuckle extract 0.5

[0369] (31) Erythritol 1

[0370] (32) Trehalose 1

[0371] (33) Trimethylglycine 1

[0372] (34) Menthol 0.2

[0373] ※30: (Evaluation method) 1. The transmittance measured by the method described in the transmittance of powder is 15%, and the average particle size is 25nm

[0374] ※31: X-CERA TiO2 R250 (manufactured by Daito Chemical Industry Co., Ltd.) Average particle size 250nm

[0375] ※32: FHS-3 TiO2 MP-1133 (manufactured by Daito Chemical Industry Co., Ltd.) Average particle size 250nm

[0376] ※33: MST-1 TiO2 R250 (manufactured by Daito Chemical Industry Co., Ltd.) Average particle size 250nm

[0377] ※34: PERFORMALENE 500 (manufactured by New Phase Technologies)

[0378] ※35: MULTIWAX W445 (made by Sonneborn)

[0379] ※36: PARACERA 256 (Paramelt)

[0380] ※37: KF-96A-5cs (manufactured by Shin-Etsu Chemical Co., Ltd.)

[0381] ※38: COSME SILICA CQ4 (manufactured by Fuji Silysia Chemical Co., Ltd.) Average particle size 4 μm

[0382] ※39: SE-TA-EX (manufactured by Miyoshi Chemicals Co., Ltd.) Average particle size: 15 μm.

[0383] (Manufacturing method)

[0384] A: Components (5) to (16) are uniformly mixed and dissolved at 90°C.

[0385] B: Components (1) to (4) and components (17) to (22) are uniformly mixed and dispersed using a roll mill, and then mixed with A.

[0386] C: Mix ingredients (23) to (34) uniformly.

[0387] D: C was added to B at 90°C, and emulsified using a disperser at 2000 rpm and 90°C for 5 minutes.

[0388] E: D is filled into a container and cooled to solidify to obtain a water-in-oil type sunscreen stick.

[0389] The water-in-oil type sunscreen stick of Example 19 was excellent in uniformity of the coating film, water resistance, stability over time, and usability.

Claims

1. A water-in-oil composition comprising the following components (A) to (D): Component (A) 5 to 30% by mass of zinc oxide surface-treated with silica and a hydrophobic treatment agent Component (B) is one or more polar oils selected from the group consisting of 2-ethylhexyl p-methoxycinnamate, 2-{4-(diethylamino)-2-hydroxybenzoyl}hexyl benzoate, 2,4-bis[{4-(2-ethylhexyloxy)-2-hydroxy}-phenyl]-6-(4-methoxyphenyl)-(1,3,5)-triazine, 2,4,6-tris[{4-(2-ethylhexyloxycarbonyl)anilino]-1,3,5-triazine, myristyl alcohol, alkyl benzoate (C12-15), diisopropyl sebacate, isononyl isononanoate, diisostearyl malate, tri(caprylic acid / capric acid)glyceryl, tri(2-ethylhexanoic acid)glyceryl, triisostearate, triisopalmitic acid, tricaprylin, isopropyl myristate and diisopropyl adipate Ingredient (C) Silicone oil Ingredient (D) water; When the component (A) is mixed at 0.25% by mass in a water / ethanol solvent (mass ratio water:ethanol=3:1), the transmittance of light with a wavelength of 700 nm is 0.8 to 20%. The content of the component (B) is 2 to 30% by mass The content of the component (C) is 3 to 40% by mass, The content of the surfactant is 1% by mass or less, and the surfactant is a nonionic surfactant, The content mass ratio (B) / (C) of the above-mentioned component (B) and the above-mentioned component (C) is 0.1-8.

2. The water-in-oil composition according to claim 1, wherein The water-in-oil composition is a Pickering emulsion.

3. The water-in-oil composition according to claim 1 or 2, wherein The content of the component (B) is 5 to 30% by mass.

4. The water-in-oil composition according to claim 1 or 2, wherein The content mass ratio (B) / (C) of the component (B) to the component (C) is 1 to 3.

3.

5. The water-in-oil composition according to claim 1 or 2, wherein The average particle size of the emulsion droplets of the water-in-oil composition is 10 to 500 μm.

6. The water-in-oil composition according to claim 1 or 2, wherein As the component (B), a polar oil that is liquid at 25°C and a polar oil that is solid at 25°C are contained, wherein the polar oil that is liquid at 25°C is selected from 2-ethylhexyl p-methoxycinnamate, alkyl benzoate (C12-15), diisopropyl sebacate, isononyl isononanoate, diisostearyl malate, tri(caprylic acid / capric acid)glyceryl, tri(2-ethylhexanoic acid)glyceryl, triisostearate, triisopalmitin, tricaprylin, isopropyl myristate and The solid polar oil at 25° C. is one or more selected from 2-{4-(diethylamino)-2-hydroxybenzoyl}benzoic acid hexyl ester, 2,4-bis[{4-(2-ethylhexyloxy)-2-hydroxy}-phenyl]-6-(4-methoxyphenyl)-(1,3,5)-triazine, 2,4,6-tris[{4-(2-ethylhexyloxycarbonyl)anilino]-1,3,5-triazine and myristyl alcohol.

7. The water-in-oil composition according to claim 1 or 2, wherein The content mass ratio of the water phase to the oil phase (water phase) / (oil phase) is 0.3-5.

8. The water-in-oil composition according to claim 1 or 2, wherein The content mass ratio of the aqueous phase to the component (A) (aqueous phase) / (A) is 0.75-10.

Citation Information

Patent Citations

  • Thermal printer

    JP1988034167A

  • Oil-in-water fine dispersion system without emulsifier

    JP2001518111A

  • Water-in-oil type emulsion composition

    JP2008208045A

  • W / o type emulsion sunscreen cosmetic

    JP2013043875A

  • Sunscreen cosmetics

    JP2016145157A